Calcite formation on steamed concrete surfaces and its potential for sealing cracks. (10th April 2019) - Zemann, M.; Herrmann, N.; Dehn, F.
Highlights: Assessment of calcite formation on steam flown concrete crack surfaces. Combined evaluation of crack healing by mineralogical analysis and flow measurement. Calcite layers increases along the steam exposure time up to a stable level. Evidence of mass flow reduction in steam flown cement cracks by autogenous healing. Abstract: Under accidental conditions, concrete containments of nuclear power plants often remain as final barrier to the environment. To evaluate the contribution of self-healing processes of cracked concrete containments, small scale experiments were conducted for given accident scenarios to examine the mineralogical processes on cement crack surfaces in contact with hot steam-air mixes. The surface analyses with ESEM, µ-RFA and microscope showed a calcite formation, where layer thicknesses increased along the exposure times until reaching a stable level. The potential for crack healing was principally demonstrated through flow measurements, where the outflowing mass decreased during the experiments along with increasing calcite formation.